Level of awareness in the use of artificial intelligence to improve the teaching process Sulaimani University teachers - كریم, م.م. شاهۆ خوارحم كریم (Sulaimani Journal for Humanities, 2025)
The aim of this study is to determine the level of awareness of teachers of Sulaimani University about the use of artificial intelligence in the teaching process, as well as to determine the statistical differences in the use of artificial intelligence The importance and effectiveness of using artificial intelligence to improve the teaching process. To achieve these goals, the researcher used descriptive method based on analytical method and using previous research, prepared a criterion on the use of artificial intelligence in teaching process, after evaluation by a number of experts in computer science, education and media (0.97) was the value. In order to collect data and information, the researcher implemented the measure through a survey form on a sample of teachers of Sulaimani University, which numbered (250) teachers, out of (2354) teachers in the research community for the academic year (2024-2025). After analyzing the results through SPSS-26, the study concluded that the awareness of the use of artificial intelligence to improve the teaching process among teachers of Sulaimani University is very good, but their knowledge about artificial intelligence tools is moderate Artificial intelligence reflects on improving the teaching process, so that the more artificial intelligence tools are used in teaching processes, the better learning occurs.
Keywords: Awareness; Usage of Artificial Intelligence; Teaching process; University teacher